2018
DOI: 10.1038/s41598-018-30696-z
|View full text |Cite
|
Sign up to set email alerts
|

Including planocerid flatworms in the diet effectively toxifies the pufferfish, Takifugu niphobles

Abstract: Beginning with the larval stages, marine pufferfish such as Takifugu niphobles contain tetrodotoxin (TTX), an extremely potent neurotoxin. Although highly concentrated TTX has been detected in adults and juveniles of these fish, the source of the toxin has remained unclear. Here we show that TTX in the flatworm Planocera multitentaculata contributes to the toxification of the pufferfish throughout the life cycle of the flatworm. A species-specific PCR method was developed for the flatworm, and the specific DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Previously, we had reported that T. niphobles (at present Takifugu alboplumbeus ) juveniles and adults/young became toxic by feeding on P. multitentaculata larvae and adults, respectively [29]. Our findings in this study now show that the pufferfish also feed on P. multitentaculata egg plates, and thus, the flatworm egg plates appear to be an additional source of TTX.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Previously, we had reported that T. niphobles (at present Takifugu alboplumbeus ) juveniles and adults/young became toxic by feeding on P. multitentaculata larvae and adults, respectively [29]. Our findings in this study now show that the pufferfish also feed on P. multitentaculata egg plates, and thus, the flatworm egg plates appear to be an additional source of TTX.…”
Section: Resultssupporting
confidence: 67%
“…600 bp) were amplified by PCR using pairs of primers HRNT-F2 (5′-AGTTC AAGAG TACGT GAAAC C-3′) / HRNT-R2 (5′-AACAC CTTTT GTGGT ATCTG ATGA-3′) and HRpra2 (5′-AATAA GTATC ATGTA RACTD ATRTC T-3′) / HRprb2-2 (5′-GDGGV TTTGG DAATT GAYTA ATACC TT-3′), respectively [32]. PCR amplification and sequencing of the PCR products were conducted following the protocol of our previous report [29]. The flatworm 28S rRNA and COI gene sequences have been submitted to the DDBJ/EMBL/GenBank databases under the accession numbers LC489235–LC489238.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations